Species Diversity and Distributional Pattern of Cockroaches in Lahore, Pakistan - Hafsa Memona; Farkhanda Manzoor; Saffora Riaz (Journal of Arthropod-Borne Diseases, 2017)
Background: Cockroaches are found as the most common urban pests of tropical countries, prompting economic and serious health risk problem for humans by carrying microbes and allergens, acting as vector for various pathogens of diseases. The present study was conducted from April 2013 to March 2014 in various human dwelling localities of urban area of district Lahore, Pakistan. Methods: Cockroaches were collected randomly by hand, food baited and sticky traps throughout the year. Four species of cockroaches (Periplaneta Americana (P. amercana), Blattella germanica (B. germanica), Blatta orientalis (B. orientalis), and Blatta lateralis (B. lateralis) were collected and identified from the study site. Results: B. germanica was the most dominant indoor species with highest diversity indices in study areas. Overall cockroach species diversity was highest in July–September, 2013 with highest Simpson index of diversity and Shannon index as well. P. americana was found second broadly distributed in the study area followed by B. orientalis and B. lateralis were intermediately distributed in residential areas and narrowly distributed in hospitals. Residential areas and hospitals were highly infested with B. germanica followed by P. americana. Population index of B. germanica for hospitals was double than residential areas. B. lateralis was observed as displacing B. orientalis in outdoor habitat through competing with its habitat and food sources. Conclusion: The infestation rate of different species depends on availability of food sources, sanitary conditions and climatic conditions. Cockroach infestation can be controlled with knowledge about their biology and behavior, attention to sanitation and effective use of commercial insecticides.